Hypothetic Reconstruction of The Development of The Defensive Structures of The Middle Town of Rohatyn in 15th−17th Centuries - Bevz, Mykola (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2018)
On the Rohatyn example we want to demonstrate: how the battles, assault and destruction of the town influenced the character of its urban and architectural development (as shown by the example of the Battle of 1509 and the events of World War I); how important the fortification element was in the past in towns of Halychyna region; what methodology can be used to reconstruct the stages of development of urban fortifications, given that today they are almost completely lost; the importance of a thorough analysis of the current state of the territory and the town’s relief, the study of historical documents, analysis of cartographic materials and iconographic sources for the theoretical reconstruction of stages of development of fortifications. The town of Rohatyn belongs to the oldest urban locations that existed according to the German (Magdeburg) law in the territory of Western Ukraine. The great chronological depth of the town’s urban structure has been often mentioned by researchers. However, academic literature does not yet fully cover the changes made to the planning of the town’s structure during the 15th−17th centuries. Similarly, the stages of development of the town’s defensive lines were not identified, although historical documents contain many references to the existence of fortifications around the middle town and the castle. Existing documentation only describes the urban changes in general terms, with researchers not yet having organized them into specific planning schemes. In our present work, we set our goal as the reconstruction of the different stages of development of fortifications of the original walled medieval town of Rohatyn. We use the following methodology: analysis of the town’s planning structure based on both historical and contemporary maps; studies of the remains of fortifications in the current landscape; comparison of field studies with data from cartographic analysis to references to the defensive objects found in historical documents; studies of analogical landmarks; and graphical reconstruction of stages of development of fortifications. According to our research, the fortification history of the town can be divided into four main stages. 1st stage – between 1415 AD (date of the town’s founding) and 1509 AD (complete demolition of the town as a result of the attack of the Wallachian-Turkish army). 2nd stage – from 1509 AD to approximately 1539 AD. The town within the walls of the surrounding fortification is restored on the basis of new royal privileges given in 1523, 1535 and 1539. The town is able to develop, with new fortifications being built around the residential and commercial districts of the town and the castle. 3rd stage – from 1539 AD to the end of the 16th century. A new district called the “New Town” was created to the west of the old walled town, with a new belt of earth bastion fortifications. At the end of this period, the bank form of the defenses was modernized into the bastion forms. 4th stage – the 17th century. The town’s fortifications continue to be maintained in good condition and upgraded. The territorial expansion of the town to the south led to the emergence of new residential neighborhoods and the creation of additional bastion fortifications to the east and south of the borders of the New Town. Our research has shown that Rohatyn is a unique town in aspects of the development of fortification systems in the 15th and 17th centuries in Ukraine.